X-linked hypophosphatemic rickets: a new mutation - Maio,Patrícia (2021)
Abstract Phosphopenic rickets may be caused by mutations in the PHEX gene (phosphate regulating endopeptidase homolog X-linked). Presently, more than 500 mutations in the PHEX gene have been found to cause hypophosphatemic rickets. The authors report a clinical case of a 4-year-old girl with unremarkable family history, who presented with failure to thrive and bowing of the legs. Laboratory tests showed hypophosphatemia, elevated alkaline phosphatase, normal calcium, mildly elevated PTH and normal levels of 25(OH)D and 1.25(OH)D. The radiological study showed bone deformities of the radius and femur. Clinical diagnosis of phosphopenic rickets was made and the genetic study detected a heterozygous likely pathogenic variant of the PHEX gene: c.767_768del (p.Thr256Serfs*7). This variant was not previously described in the literature or databases. Knowledge about new mutations can improve patient’s outcome. Genetic analysis can help to establish a genotype-phenotype correlation.